O języku przyrodniczym i łowieckim w komunikacji międzykulturowej. Studium przypadku - Matulewska, Aleksandra (Języki specjalistyczne w komunikacji interkulturowej, 2020)
Not much is written about communication in the languages of natural sciences and hunting. Only a few authors explore literature and the language of forestry or hunting (Dynak 1988, 1991a, 1991b, 1993, 1994, 2004, 2012; Jóźwiak Z. 2004; Jóźwiak J. 2013; Kloc 2019; Kościelniak-Marszał 2013; Pajewska 2003; Przybecki 2008). At the same time, these languages, both in Poland and abroad, have not been researched into so far from a broader comparative perspective in the field of intercultural communication. First of all, monolingual dictionaries are available on the market (e.g. Hoppe 1970; Gawin 2016; Jóźwiak; Biały 1994; Kozłowski 1996; Krzemień 1986; Szałapak 2004). In addition, you can find several bilingual dictionaries of the forestry or hunting language in Polish-English (Kloc 2013, 2015; Witkowska 2010), Polish-German (Niedbał 1917; Żeromski 1990; Klin et al. 2006) pairs and vice versa, but there are no dictionaries for other language pairs, e.g. Polish-French. There are also no papers devoted to communication problems, despite the fact that books on nature sciences and hunting are translated from various languages into Polish, and there is a market demand for translators ensuring effective interlingual communication during hunting trips. The aim of the work is to present the problems of intercultural communication in the field of natural sciences and hunting language. The results presented in the work were obtained by analyzing the work of students participating in a specialist translation course. A qualitative analysis of the mistakes made by students has been made and conclusions have been drawn as to how well a student of philological studies is prepared to translate natural science texts, including hunting texts.